Sintered body and its manufacturing method
A zirconia-based sintered body stabilized with scandium, yttrium, and lanthanoid elements addresses transparency and mechanical strength issues, enabling high-performance display screen materials through controlled crystal orientation and processing techniques.
Patent Information
- Application Number
- JP2022579496
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-02-03
- Filing Date
- 2022-01-27
- Publication Date
- 2025-01-29
- Estimated Expiration
- 2042-01-27
AI Technical Summary
Conventional zirconia-based sintered bodies with mixed cubic and tetragonal crystal phases lack sufficient transparency and mechanical strength, failing to meet the demands of advanced applications such as reinforced glass and display materials.
A sintered body composed of zirconia stabilized with scandium, yttrium, and lanthanoid rare earth elements, with controlled crystal orientation and high relative density, achieving transparency and mechanical strength through precise sintering and HIP processing.
The sintered body exhibits high transparency (50-72% transmittance) and mechanical strength (800 MPa bending strength, 4 MPa·m0.5 toughness) suitable for display screen materials, overcoming the limitations of conventional zirconia.
Smart Images

Figure 0007624020000003 
Figure 0007624020000004 
Figure 0007624020000005
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a sintered body made of zirconia having a tetragonal main phase and a method for producing the same. [Background technology]
[0002] Zirconia is mainly composed of a crystal phase having either monoclinic, tetragonal or cubic as a main phase, and is being applied and studied for applications according to the characteristics of each crystal phase. For example, for applications such as structural materials requiring mechanical properties, sintered bodies made of zirconia having tetragonal as a main phase are being applied and studied (e.g., Patent Document 1). On the other hand, for applications requiring optical properties such as cover materials, particularly applications requiring high transparency, sintered bodies made of zirconia having cubic as a main phase are being applied and studied (e.g., Patent Document 2). Furthermore, for applications such as decorative materials, dental materials and medical materials requiring moderate mechanical properties and optical properties, sintered bodies made of zirconia having a crystal phase in which tetragonal and cubic crystals are mixed are being applied and studied (e.g., Patent Document 3). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2000-95564 A [Patent Document 2] JP 2012-174053 A [Patent Document 3] JP 2017-148374 A Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, there has been an increasing demand for alternative materials to reinforced glass and other materials used as display screen materials, and even for materials with properties that surpass these. Conventional sintered bodies made of zirconia with a mixed crystal phase of tetragonal and cubic crystals, such as those in Patent Document 3, have high total transmittance due to the inclusion of tetragonal crystals, but insufficient linear transmittance, and therefore could not meet these demands. Conventional sintered bodies made of zirconia with a cubic crystal as the main phase, such as those in Patent Document 2, have difficulty in improving mechanical properties, and therefore also could not meet these demands.
[0005] An object of the present disclosure is to provide at least one of a sintered body having higher transparency than conventional sintered bodies made of zirconia having a tetragonal main phase and a manufacturing method thereof, and further a sintered body made of zirconia having a tetragonal main phase and having transparency comparable to that of display screen materials such as tempered glass and a manufacturing method thereof. [Means for solving the problem]
[0006] The present invention is as described in the claims, and the gist of the present disclosure is as follows. [1] A sintered body comprising zirconia having one or more stabilizing elements selected from scandium, yttrium, and lanthanoid rare earth elements dissolved therein and having a tetragonal crystal structure as the main phase, the zirconia having a relative density of 99.9% or more, and further characterized in that the zirconia has (a) an average crystal grain size of 10 nm or more and 100 nm or less and is non-oriented, or (b) an average crystal grain size of 100 nm or more and 1000 nm or less and the degree of orientation of either the (100) plane or the (001) plane is 90% or more. [2] The sintered body according to the above [1], having an in-line transmittance of 50% or more and 72% or less at a sample thickness of 0.2 mm and a wavelength of 500 to 800 nm. [3] The sintered body according to the above [1] or [2], having a bending strength of 800 MPa or more. [4] Fracture toughness value (K IC ) is 4MPa m 0.5 The sintered body according to any one of the above [1] to [3]. [5] A method for producing a sintered body which is made of zirconia having a tetragonal crystal structure as a main phase and which is solid-dissolved with one or more stabilizing elements selected from scandium, yttrium, and lanthanoid rare earth elements, has a relative density of 99.9% or more, and the zirconia has an average crystal grain size of 10 nm or more and 100 nm or less, and is non-oriented, comprising: A method for producing a sintered body, comprising: a pre-sintering step of sintering a molded body made of zirconia powder having an average primary particle size of 5 nm or more and 50 nm or less, and containing one or more stabilizing elements selected from scandium, yttrium, and lanthanoid rare earth elements, in the atmosphere at 1000°C or more and 1250°C or less to obtain a pre-sintered body; and a HIP treatment step of hot isostatic pressing at 1000°C or more and 1250°C or less. [6] A method for producing a sintered body, which is made of zirconia having a tetragonal crystal phase as a main phase and containing one or more stabilizing elements selected from scandium, yttrium, and lanthanoid rare earth elements as a solid solution, has a relative density of 99.9% or more, and the zirconia has an average crystal grain size of 100 nm or more and 1000 nm or less, and has an orientation degree of 90% or more in either the (100) plane or the (001) plane, A method for producing a sintered body, comprising: a pre-sintering step of sintering an oriented molded body of zirconia powder containing one or more stabilizing elements selected from scandium, yttrium, and lanthanoid rare earth elements at 1100°C to 1300°C to obtain a pre-sintered body, the molded body being composed of primary particles having a minor axis of 10 nm to 100 nm, a major axis of 20 nm to 1000 nm, and an aspect ratio of the major axis to the minor axis of 2 or more; and a HIP treatment step of hot isostatically pressing the pre-sintered body at 1100°C to 1350°C. [7] The method according to [5] or [6] above, wherein the relative density of the pre-sintered body is 94% or more and 99% or less. [8] A display screen material comprising the sintered body according to any one of [1] to [4] above. [9] The display screen material according to [8] above, having a thickness of 0.1 mm or more and 1.0 mm or less.
[10] A display device comprising the display screen material described in [9] above. Effect of the Invention
[0007] The present disclosure makes it possible to provide at least one of a sintered body having higher transparency than a conventional sintered body made of zirconia having a tetragonal main phase and a manufacturing method thereof, and a sintered body made of zirconia having a tetragonal main phase and having transparency comparable to that of display screen materials such as tempered glass and a manufacturing method thereof. [Brief description of the drawings]
[0008] [Figure 1] A schematic diagram showing the transmission of incident light through conventional zirconia with a tetragonal main phase. [Diagram 2] Schematic diagram showing the transmission state of incident light through non-oriented zirconia of this embodiment. [Diagram 3] Schematic diagram showing the transmission state of incident light through highly oriented zirconia of this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, the present disclosure will be described with reference to an example of an embodiment. The terms used in this embodiment are as follows: "The main phase is tetragonal" means that the zirconia has the highest proportion of tetragonal crystals among the monoclinic, cubic, and tetragonal crystals. The proportion of tetragonal crystals in the zirconia crystal phase can be calculated by the Rietveld method using the RIETAN-FP (Reference: F. Izumi, "The Rietveld Method", Ed. by RA Young, Oxford University Press, Oxford (1993) Chap. 13.) analysis program for the X-ray diffraction (XRD) profile of the sintered body. In zirconia with tetragonal crystals as the main phase, the proportion of tetragonal crystals calculated above is 50% by mass or more. The "average crystal grain size" refers to a value calculated by the planimetric method described in Yamaguchi Takashi, Ceramics, 19, 520-529 (1984) using an electron microscope. The "degree of orientation" is a value determined from the XRD profile of a sintered body by focusing on the diffraction lines of only tetragonal crystals and using the following formula.
number
number
[0010] The sintered body of this embodiment will be described below. The present embodiment is a sintered body made of zirconia having one or more stabilizing elements selected from scandium, yttrium, and lanthanoid rare earth elements dissolved therein and having a tetragonal main phase, and characterized in that the zirconia has a relative density of 99.9% or more, and further has the following characteristics: (a) an average crystal grain size of 10 nm or more and 100 nm or less and is non-oriented, or (b) an average crystal grain size of 100 nm or more and 1000 nm or less and the degree of orientation of either the (100) plane or the (001) plane is 90% or more.
[0011] The sintered body of this embodiment is a so-called zirconia sintered body, further a partially stabilized zirconia, made of zirconia in which one or more stabilizing elements selected from scandium, yttrium, and lanthanoid rare earth elements are dissolved. The stabilizing element is an element that has a function of stabilizing zirconia by dissolving in the zirconia, and is one or more selected from scandium, yttrium, and lanthanoid rare earth elements, preferably yttrium.
[0012] In this embodiment, it may be confirmed that the stabilizing element is dissolved in zirconia by containing the stabilizing element and by not having an independent XRD peak of the stabilizing element in the XRD pattern.
[0013] The zirconia constituting the sintered body of the present embodiment has a tetragonal phase as the main phase, and may be composed of a tetragonal phase and a cubic phase. By having a tetragonal phase as the main phase, the sintered body has mechanical properties suitable for use as an exterior part such as a cover member or a housing.
[0014] The zirconia is characterized by (a) an average crystal grain size of 10 nm to 100 nm and non-oriented (hereinafter also referred to as "non-oriented zirconia"); or (b) an average crystal grain size of 100 nm to 1000 nm and an orientation degree of either the (100) plane or the (001) plane of 90% or more (hereinafter also referred to as "highly oriented zirconia"). When the zirconia is non-oriented zirconia or highly oriented zirconia, the birefringence derived from the tetragonal crystal structure can be extremely suppressed, and as a result, the zirconia has high mechanical properties derived from the tetragonal crystal, as well as high linear transmittance despite being a tetragonal crystal. As shown in FIG. 1, in non-oriented zirconia with a tetragonal crystal as the main phase, the refractive index differs with respect to the crystal orientation because the tetragonal crystal is an anisotropic crystal structure. Due to the birefringence caused by this, light incident on the non-oriented zirconia is scattered and diffused in various directions by the crystal grain boundaries. As a result, it is known that unoriented zirconia having a tetragonal crystal as the main phase has low transparency. In contrast, as shown in FIG. 2, the unoriented zirconia of this embodiment has a crystal grain size sufficiently smaller than that of light in the visible light region (particularly, light having a wavelength of 500 to 800 nm), so that the effect of birefringence is substantially small and the linear transmittance is high, even though the crystal structure has a different refractive index depending on the crystal orientation. Also, as shown in FIG. 3, the highly oriented zirconia of this embodiment has a tetragonal crystal as the main phase, but the crystal orientation of the tetragonal crystal is in a fixed direction relative to the direction of penetration of the incident light, so that the refractive index difference is substantially small to the extent that it cannot be confirmed. Therefore, the effect of scattering and diffusing light in various directions due to the crystal grain boundaries is small to the extent that it cannot be visually recognized. The linear transmittance of the sintered body of this embodiment is 50% to 72% at a sample thickness of 0.2 mm and a wavelength of 500 to 800 nm.
[0015] The sintered body of this embodiment has a relative density of 99.9% or more. If the relative density is less than 99.9%, there will be too many defects such as pores that are the source of light scattering, and even if the sintered body is non-oriented zirconia or highly oriented zirconia, the light transmittance will be low. The relative density will be 100% or less.
[0016] The sintered body of this embodiment has high mechanical properties derived from the tetragonal crystal structure, and the bending strength is preferably 800 MPa or more, and can be 800 MPa or more and 2000 MPa or less, for example. In addition, the sintered body of this embodiment has a fracture toughness value (K IC ) is 4MPa m 0.5 It is preferable that the temperature is 4 MPa m or higher. 0.5 More than 6MPa m 0.5 The following can be exemplified.
[0017] The sintered body of the present embodiment can be used for known applications of sintered bodies, and can be preferably used as a display screen material. When used as a display screen material, the sintered body of the present embodiment may be formed into a desired shape, for example, a display screen material having a thickness of 0.1 mm or more and 1.0 mm or less.
[0018] A display screen material made of the sintered body of this embodiment can be used as a display device equipped with such a display or touch panel.
[0019] Next, a method for producing the sintered body of this embodiment will be described. The sintered body made of non-oriented zirconia in this embodiment can be produced, for example, by a production method including a pre-sintering step of sintering a molded body made of zirconia powder having an average primary particle size of 5 nm or more and 50 nm or less and containing one or more stabilizing elements selected from scandium, yttrium, and lanthanoid rare earth elements in the atmosphere at 1000° C. or more and 1250° C. or less to obtain a pre-sintered body, and a HIP treatment step of hot isostatic pressing at 1000° C. or more and 1250° C. or less.
[0020] In addition, the sintered body made of highly oriented zirconia in this embodiment can be produced, for example, by a production method including a pre-sintering step of sintering an oriented molded body of zirconia powder containing one or more stabilizing elements selected from scandium, yttrium, and lanthanoid rare earth elements at 1100°C to 1300°C to obtain a pre-sintered body, the molded body being made of primary particles having a short axis of 10 nm to 100 nm, a long axis of 20 nm to 1000 nm, and a long axis length relative to the short axis length (aspect ratio) of 2 or more, and a HIP treatment step of hot isostatically pressing the pre-sintered body at 1100°C to 1350°C.
[0021] The green body to be subjected to the preliminary sintering step may be a green compact obtained by molding powder by any method, and examples of the molding method include any molding method such as uniaxial pressing, slip casting, sheet molding, injection molding, cold isostatic pressing, etc. In addition, when the powder is oriented and molded, the powder may be molded while applying a magnetic field during molding.
[0022] The powder constituting the molded body may be a powder synthesized by any method such as coprecipitation, hydrolysis, hydrothermal synthesis, etc. Examples of the powder include a powder obtained by hydrolyzing one or more selected from the group consisting of zirconium oxychloride, zirconyl nitrate, zirconium chloride, and zirconium sulfate, and a powder obtained by mixing one or more selected from the group consisting of zirconium oxychloride, zirconyl nitrate, zirconium chloride, and zirconium sulfate with an alkali component and co-precipitating the mixture.
[0023] The relative density of the pre-sintered body is preferably 94% or more and 99% or less, and in the pre-sintering step, the molded body may be pre-sintered under any conditions under which the relative density of the obtained pre-sintered body falls within the range. Examples of pre-sintering conditions include heat treatment in air at 1000°C or more or 1100°C or more and 1300°C or less or 1250°C or less.
[0024] The HIP treatment step may be carried out under any conditions under which the relative density of the resulting sintered body is 99.9% or more, such as in an argon atmosphere at 1000° C. or more or 1100° C. or more, 1350° C. or less or 1250° C. or less, and at 50 MPa or more and 200 MPa or less. Increasing the temperature of the HIP treatment tends to increase the average crystal grain size. [Industrial Applicability]
[0025] The sintered body of the present embodiment can be used for known applications of zirconia, such as optical materials, dental materials, structural materials, decorative materials, etc., and can be preferably used as a display screen material.
Claims
1. A sintered body comprising zirconia having a tetragonal main phase and containing one or more stabilizing elements selected from scandium, yttrium, and lanthanoid rare earth elements as a solid solution, the zirconia having a relative density of 99.9% or more, an average crystal grain size of 100 nm or more and 1000 nm or less, and an orientation degree of either the (100) plane or the (001) plane of 90% or more.
2. 2. The sintered body according to claim 1, wherein the linear transmittance at a sample thickness of 0.2 mm and a wavelength of 500 to 800 nm is 50% or more and 72% or less.
3. 3. The sintered body according to claim 1, having a bending strength of 800 MPa or more.
4. Fracture toughness value (K IC ) is 4MPa m 0.5 The sintered body according to any one of claims 1 to 3.
5. A method for producing a sintered body, which is made of zirconia having a tetragonal main phase containing one or more stabilizing elements selected from scandium, yttrium, and lanthanoid rare earth elements as a solid solution, has a relative density of 99.9% or more, and the zirconia has an average crystal grain size of 100 nm or more and 1000 nm or less, and has an orientation degree of 90% or more in either a (100) plane or a (001) plane, A method for producing a sintered body, comprising: a pre-sintering step of sintering an oriented molded body of zirconia powder containing one or more stabilizing elements selected from scandium, yttrium, and lanthanoid rare earth elements at 1100°C to 1300°C to obtain a pre-sintered body, the molded body being composed of primary particles having a minor axis of 10 nm to 100 nm, a major axis of 20 nm to 1000 nm, and a major axis length relative to the minor axis length (aspect ratio) of 2 or more; and a HIP treatment step of hot isostatically pressing the pre-sintered body at 1100°C to 1350°C.
6. The method according to claim 5, wherein the relative density of the pre-sintered body is 94% or more and 99% or less.
7. A display screen material comprising the sintered body according to claim 1 .
8. 8. The display screen material according to claim 7, having a thickness of 0.1 mm or more and 1.0 mm or less.
9. A display device comprising the display screen material according to claim 8.
Citation Information
Patent Citations
Zirconia ceramic and method for preparing zirconia ceramic through multitime sintering
CN108751989A
Monoclinic zirconia compacted sintered product and its production
JP1999240754A
Zirconia sintered body, its production and material for pulverizing member
JP2000095564A
Grain-oriented ceramics sintered compact, and production method therefor
JP2003112974A
Translucent ceramic and method for producing the same
JP2006315878A